2022
DOI: 10.1371/journal.pone.0262441
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression analysis following olfactory learning in honeybee (Apis mellifera L.)

Abstract: Insects change their stimulus-response through the perception of associating these stimuli with important survival events such as rewards, threats, and mates. Insects develop strong associations and relate them to their experiences through several behavioral procedures. Among the insects, Apis species, Apis mellifera ligustica are known for their outstanding ability to learn with tremendous economic importance. Apis mellifera ligustica has a strong cognitive ability and promising model species for investigatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 91 publications
(111 reference statements)
1
6
0
1
Order By: Relevance
“…Nonetheless, the MRJP-like genes, as part of this family, seem to be restricted to Hymenoptera 56 . Even though these genes have been associated with olfactory learning—particularly regarding mrjp1 expression in the mushroom body (Kenyon cells) 31 , 57 , 58 —and functional studies have shown that MRJPs may have immunoregulatory and antibacterial effects 56 , in bees, MRJPs are mostly associated with larvae feeding, development and with the regulation of phenotypic plasticity and age-polyethism in workers 59 . In honeybees, MRJPs are known to be essential components of the larvae diet, with MRJP1–3 and 5 being the most abundant proteins of larval food 56 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the MRJP-like genes, as part of this family, seem to be restricted to Hymenoptera 56 . Even though these genes have been associated with olfactory learning—particularly regarding mrjp1 expression in the mushroom body (Kenyon cells) 31 , 57 , 58 —and functional studies have shown that MRJPs may have immunoregulatory and antibacterial effects 56 , in bees, MRJPs are mostly associated with larvae feeding, development and with the regulation of phenotypic plasticity and age-polyethism in workers 59 . In honeybees, MRJPs are known to be essential components of the larvae diet, with MRJP1–3 and 5 being the most abundant proteins of larval food 56 .…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila , for instance, Unc80 is necessary for circadian rhythmicity 124 . It is thought that Unc80 may also be involved in bee learning and memory 31 . The gene Hr38, a nuclear receptor , is involved in the transcriptional control of the dopamine synthesis pathway 127 , the cuticle gene expression 128 , and the ecdysteroid signaling pathways 129 .…”
Section: Box 1: Orthologs Upregulated In C Waltheriae ...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this belief has not been scientifically proven [21]. The acceptance of artificial queen cells by bees is influenced by various factors, including the season of RJ production and genetic factors like the breed [22,23]. Also, the availability of food supplies, particularly pollen and nectar, fluctuates throughout the year, affecting the stimulation of bee glands.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, mutations in Unc80 have been shown to impact various biological processes. For instance, in honeybees, differences in Unc80 expression, observed through NGS-Seq of brains from odor-learning tasks, suggest a correlation between Unc80 and olfactory learning [ 32 ]. In C. elegans , mutations in Unc80 led to impaired avoidance behavior to Methyl salicylate, which could be significantly mitigated by neuron-specific transgenic rescue, further underscoring Unc80 ’s role in neural function [ 33 ].…”
Section: Introductionmentioning
confidence: 99%